Effect of Gentamicin Ointment in Patients with Nagashima-type Palmoplantar Keratosis: A Double-blind Vehicle-controlled Study - Yue Li; Xia Yu; Chaolan Pan; Yumeng Wang; Jianwen Han; Zhirong Yao; Ming Li (Medical Journals Sweden, 2021)
Gentamicin ointment has potential in the treatment of Nagashima-type palmoplantar keratosis. However, there is a lack of reliable study data. The aim of this study was to perform a prospective, randomized, double-blinded, contralateral, vehicle-controlled clinical trial. A total of 20 subjects diagnosed with Nagashima-type palmoplantar keratosis by genetic test, who carried nonsense mutations, enrolled in the 30-day study. Gentamicin ointment was applied to the hand and foot on one side of the body, and vehicle ointment was applied to the hand and foot on the other side. The choice of hand and foot in each subject was randomly allocated. The severity of the patient's skin lesions and quality of life were assessed by a blinded evaluator, using the Dermatology Life Quality Index, visual analogue scale scores and digital photography. Gentamicin ointment treatment resulted in a significant improvement in symptoms of hyperkeratosis and foul smell compared with vehicle. No difference was found in the effect on erythema between gentamicin and vehicle. In conclusion, gentamicin ointment demonstrated positive responses and good tolerance in treating Nagashima-type palmoplantar keratosis caused by nonsense mutations.